Secular variation in Late Cretaceous carbon isotopes: a new delta C-13 carbonate reference curve for the Cenomanian-Campanian (99.6-70.6 Ma) - Jarvis, I; Gale, A; Jenkyns, H; Pearce, M (2006)
Carbon stable-isotope variation through the Cenomanian-Santonian stages is characterized using data for 1769 bulk pelagic carbonate samples collected from seven Chalk successions in England. The sections show consistent stratigraphic trends and δ13C values that provide a basis for high-resolution correlation. Positive and negative δ13C excursions and inflection points on the isotope profiles are used to define 72 isotope events. Key markers are provided by positive δ13C excursions of up to +2‰: the Albian/Cenomanian Boundary Event; Mid-Cenomanian Event I; the Cenomanian/ Turonian Boundary Event; the Bridgewick, Hitch Wood and Navigation events of Late Turonian age; and the Santonian/Campanian Boundary Event. Isotope events are isochronous within a framework provided by macrofossil datum levels and bentonite horizons. An age-calibrated composite δ13C reference curve and an isotope event stratigraphy are constructed using data from the English Chalk. The isotope stratigraphy is applied to successions in Germany, France, Spain and Italy. Correlation with pelagic sections at Gubbio, central Italy, demonstrates general agreement between biostratigraphic and chemostratigraphic criteria in the Cenomanian-Turonian stages, confirming established relationships between Tethyan planktonic foraminiferal and Boreal macrofossil biozonations. Correlation of the Coniacian-Santonian stages is less clear cut: magnetostratigraphic evidence for placing the base of Chron 33r near the base of the Upper Santonian is in good agreement with the carbon-iso-tope correlation, but generates significant anomalies regarding the placement of the Santonian and Campanian stage boundaries with respect to Tethyan planktonic foraminiferal and nannofossil zones. Isotope stratigraphy offers a more reliable criterion for detailed correlation of Cenomanian-Santonian strata than biostratigraphy. With the addition of Campanian δ13C data from one of the English sections, a composite Cenomanian-Campanian age-calibrated reference curve is presented that can be utilized in future chemostratigraphic studies. The Cenomanian-Campanian carbon-isotope curve is remarkably similar in shape to supposedly eustatic sea-level curves: increasing δ13C values accompanying sea-level rise associated with transgression, and falling δ13C values characterizing sea-level fall and regression. The correlation between carbon isotopes and sea-level is explained by variations in epicontinental sea area affecting organic-matter burial fluxes: increasing shallow sea-floor area and increased accommodation space accompanying sea-level rise allowed more efficient burial of marine organic matter, with the preferential removal of 12C from the marine carbon reservoir. During sea-level fall, reduced seafloor area, marine erosion of previously deposited sediments, and exposure of basin margins led to reduced organic-carbon burial fluxes and oxidation of previously deposited organic matter, causing falling δ13C values. Additionally, drowning of carbonate platforms during periods of rapid sea-level rise may have reduced the global inorganic relative to the organic carbon flux, further enhancing δ13C values, while renewed platform growth during late transgressions and highstands prompted increased carbonate deposition. Variations in nutrient supply, changing rates of oceanic turnover, and the sequestration or liberation of methane from gas hydrates may also have played a role in controlling carbon-isotope ratios. © 2006 Cambridge University Press.